The naturally occurring GIP(1-30)NH2 is a GIP receptor agonist in humans. Issue 1 (10th January 2023) - Krogh, Liva S L; Henriksen, Kristine; Stensen, Signe; Skov-Jeppesen, Kirsa; Bergmann, Natasha C; Størling, Joachim; Rosenkilde, Mette M; Hartmann, Bolette; Holst, Jens J; Gasbjerg, Lærke S; Knop, Filip K
Abstract: Objective: The gut hormone glucose-dependent insulinotropic polypeptide (GIP) is an important regulator of glucose and bone metabolism. In rodents, the naturally occurring GIP variant, GIP(1-30)NH2, has shown similar effects as full-length GIP (GIP(1-42)), but its effects in humans are unsettled. Here, we investigated the actions of GIP(1-30)NH2 compared to GIP(1-42) on glucose and bone metabolism in healthy men and in isolated human pancreatic islets. Methods: Nine healthy men completed three separate three-step glucose clamps (0-60 minutes at fasting plasma glucose (FPG) level, 60-120 minutes at 1.5× FPG, and 120-180 minutes at 2× FPG) with infusion of GIP(1-42) (4 pmol/kg/min), GIP(1-30)NH2 (4 pmol/kg/min), and saline (9 mg/mL) in randomised order. Blood was sampled for measurement of relevant hormones and bone turnover markers. Human islets were incubated with low (2 mmol/L) or high (20 mmol/L) d -glucose with or without GIP(1-42) or GIP(1-30)NH2 in three different concentrations for 30 minutes, and secreted insulin and glucagon were measured. Results: Plasma glucose (PG) levels at FPG, 1.5× FPG, and 2× FPG were obtained by infusion of 1.45 g/kg, 0.97 g/kg, and 0.6 g/kg of glucose during GIP(1-42), GIP(1-30)NH2, and saline, respectively ( P = .18), and were similar on the three experimental days. Compared to placebo, GIP(1-30)NH2 resulted in similar glucagonotropic, insulinotropic, and carboxy-terminal type 1 collagen crosslinks-suppressing effects as GIP(1-42). In vitro experiments on human islets showed similar insulinotropic and glucagonotropic effects of the two GIP variants. Conclusions: GIP(1-30)NH2 has similar effects on glucose and bone metabolism in healthy individuals and in human islets in vitro as GIP(1-42).